Exploring the Meaning of Cost Based Mo Polihu Lo Limu Custom of Gorontalo People - Tri Handayani Amaliah; Abdul Rahmat (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
Cost actualization is not only involved in company activity, however, it is also involved in custom tradition which prevailed in a society. This research aims to explore the meaning of cost towards custom procession of Mo Polihu Lo Limu. Mo Polihu Lo Limu is heredity tradition which still upheld by Gorontalo people purposed to sanctify the girls. This research was qualitative research which conducted by using ethnomethodology approach. Data analysis in this research followed ethnomethodology rules, which are data reduction, data display, indexicality, reflectivity, and conclusion drawing. The research result showed that costs which included in Mo Polihu Lo Limu custom mean as alms (sadakah), pray (du’a), and realization of affection (motoliango). Costs which included in the implementation of this tradition, for Gorontalo people, aims to reach happiness in this world and the hereafter. This paper is an attempt to find empirical theory by using local wisdom culture as focus to find the meaning of cost in order to give contribution towards the development of accounting science.